2021
DOI: 10.1074/jbc.ra120.015524
|View full text |Cite
|
Sign up to set email alerts
|

Anionic amino acids support hydrolysis of poly-β-(1,6)-N-acetylglucosamine exopolysaccharides by the biofilm dispersing glycosidase Dispersin B

Abstract: The exopolysaccharide poly- β -(1→6)- N -acetylglucosamine (PNAG) is a major structural determinant of bacterial biofilms responsible for persistent and nosocomial infections. The enzymatic dispersal of biofilms by PNAG-hydrolyzing glycosidase enzymes, such as Dispersin B (DspB), is a possible approach to treat biofilm-dependent bacterial infections. The cationic charge resulting from partial de- N -acetylation of native PNAG is critical for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…At the same time, five C. striatum strains with weak biofilm-forming ability were also positive with spaDEF genes, which indicates an indefinite relationship between biofilm formation abilities and expression of pili in C. striatum . For some well-known gram-positive bacteria (including S. aureus , and Bacillus subtilis ), the bacterial extracellular matrix has been recognized to be an essential determinant in mediating biofilm formation and participating in the protection process from external insults [ 21 , 22 ]. The extracellular matrix composition was similar among different bacteria, including EPA, proteins, and eDNA, all of which participated in the process of biofilm formation in different manners [ 21 , 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, five C. striatum strains with weak biofilm-forming ability were also positive with spaDEF genes, which indicates an indefinite relationship between biofilm formation abilities and expression of pili in C. striatum . For some well-known gram-positive bacteria (including S. aureus , and Bacillus subtilis ), the bacterial extracellular matrix has been recognized to be an essential determinant in mediating biofilm formation and participating in the protection process from external insults [ 21 , 22 ]. The extracellular matrix composition was similar among different bacteria, including EPA, proteins, and eDNA, all of which participated in the process of biofilm formation in different manners [ 21 , 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For some well-known gram-positive bacteria (including S. aureus , and Bacillus subtilis ), the bacterial extracellular matrix has been recognized to be an essential determinant in mediating biofilm formation and participating in the protection process from external insults [ 21 , 22 ]. The extracellular matrix composition was similar among different bacteria, including EPA, proteins, and eDNA, all of which participated in the process of biofilm formation in different manners [ 21 , 23 25 ]. Correspondingly, degradative agents directed against the above components were developed to deter biofilm formation, including dispersin B, proteinase K, and DNase I. Biofilm matrix degradation with enzymatic degradative agents toward polysaccharides, proteins, and nucleic acids paves an efficient way of controlling or treating infections caused by biofilm-producing bacterial pathogens [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…129 The site of cleavage of the glycosidic bond (endo-or exo-) of the polysaccharide by Dispersin B depends on the nature of the substrate. [129][130][131] The active site architecture of the enzyme (PDB ID: 1YHT) 132 displays a conserved Asp-Glu dyad, where the Glu residue performs the general acid-base catalysis to hydrolyze the glycosidic bond through an oxazolinium intermediate (Figure 5A). The Asp residue assists the N-acetyl group for nucleophilic attack.…”
Section: Antimicrobial Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…Binding of the polysaccharide substrate to the active site of Dispersin B is assisted by a set of conserved residues: one Glu, three Trp, and one Tyr ( 129 ). The site of cleavage of the glycosidic bond (endo- or exo-) of the polysaccharide by Dispersin B depends on the nature of the substrate ( 129 , 130 , 131 ). The active site architecture of the enzyme (Protein Data Bank [PDB] ID: 1YHT ) ( 132 ) displays a conserved Asp-Glu dyad, where the Glu residue performs the general acid-base catalysis to hydrolyze the glycosidic bond through an oxazolinium intermediate ( Fig.…”
Section: Enzymatic Degradation Of Polysaccharides—an Emergent Approac...mentioning
confidence: 99%
“…Specifically, fully N ‐acetylated PNAG oligosaccharides (i.e. 1 ) are hydrolysed predominantly through sequential exo‐glycosidic bond cleavage at the non‐reducing end GlcNAc [31], which is enhanced by approximately three‐fold as a result of electrostatic interactions between DspB and substrates containing a cationic glucosamine (GlcN) in the +2 position relative to the site of cleavage [32]. Moreover, we found that in the presence of non‐reducing terminal GlcN (i.e.…”
Section: Introductionmentioning
confidence: 99%